A Translation Analysis Of Simple Sentence In Dreams Of Trespass Of Harem Girlhood Novel Into Indonesian Version Perempuan- Perempuan Harem - Rahmah, Qoniatur (2012)
This research studies about the translation analysis of simple sentence in Dreams of Trespass Harem Girlhood Novel into Indonesian version Perempuan- perempuan Harem. The objectives of the study are to classify the variation of simple sentence and to describe the equivalence translation of simple sentence in Dreams of Trespass Harem Girlhood Novel. This research is a descriptive qualitative research. The objects of the research are simple sentence found in Dreams of Trespass Harem Girlhood Novel and it's translation Perempuan- perempuan Harem. The data are in the forms of simple sentence used in word, clauses, and sentences. They are collected from both the books by using document method. She applies comparison method in analyzing the data of the study. The results of data analysis show that there are four variations of simple sentence, for example: simple sentence into simple sentence, simple sentence into compound sentence, simple sentence into complex sentence, simple sentence into dependence clause. These simple sentences are then classified based on their uses variation of simple sentence. From 316 data found, there are English SS into Indonesian SS 306 data or 96,83% (it can be break down as 7,6 % for interrogative; 0,95% for imperative; 0,32% for exclamation: and 91,14% for declarative sentence), the English SS into Indonesian CS 4 data or 1,2%, English SS into Indonesian SX 3 data or 0,9%, and English SS into Indonesian DC 3 data or 0, 9 %. Besides, the equivalence of translation is divided into equivalent translation and non equivalent translation. The translations are dominated with equivalent translation. From 316 data, there are there are 304 data or 96,2% that belong to equivalent translation and 12 data or 3,8 % that belong to non-equivalent translation.